A systematic review and meta-analysis on abnormal posturing among brain injury patients - Yuyu Wei; Yan Cui; Xiaojun Pang; Weijie Wang (Arquivos de Neuro-Psiquiatria)
Background Abnormal motor posturing (AMP), exhibiting as decorticate, decerebrate, or opisthotonos, is regularly noticed among children and adults.